RANCANG BANGUN SISTEM PENGAWASAN PEMAKAIAN ALAT PELINDUNG DIRI BERBASIS SINGLE BOARD COMPUTER - Hidayat, Pungky Irlan; Eka Putri, Rahmi; Rahmadya, Budi (Universitas Andalas, 2024)
Industries in Indonesia currently have a high rate of work accidents. Badan Penyelenggara Jaminan Sosial (BPJS) noted that in 2021 there were 82,000 cases of work accidents of which 88% were caused by unsafe actions and 12% were caused by unsafe conditions. Personal Protective Equipment (PPE) is one of the safety protocols that is often ignored at work. Image Processing is part of Artificial Intelligence and one of the technology developments that can be used in supervising the use of PPE workers, You Only Look Once (YOLO) is a method in image processing that can detect workers' PPE. The research is aimed at supervising the use of PPE (Safety Helmet and Safety Shoes) from workers and providing real-time warnings when workers do not use PPE completely. This research will utilize hardware in the form of a webcam, raspberry pi, speakers, and servers. As for the software, YOLOv4 will be used as a method of detecting PPE for workers and the website as a medium of information for violations committed.